1984
DOI: 10.1042/bj2220815
|View full text |Cite
|
Sign up to set email alerts
|

Polyamine levels and the activity of their biosynthetic enzymes in human erythrocytes infected with the malarial parasite, Plasmodium falciparum

Abstract: Human erythrocytes contain only trace amounts of polyamines and lack active polyamine biosynthetic enzymes. A remarkable increase in polyamine content, and in the activity of ornithine and S-adenosyl-L-methionine decarboxylases, is noted in synchronous cultures of the malarial parasite, Plasmodium falciparum. Polyamine biosynthesis reached peak values during the early trophozoite stage, whereas nucleic acid and protein synthesis occurred later in mature trophozoites. DL-alpha-Difluoromethylornithine, an irreve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 10 publications
4
47
0
Order By: Relevance
“…Polyamine concentrations are strictly regulated on transcriptional, translational and post-translational levels as well as by uptake and efflux processes [1]. Erythrocytes infected by Plasmodium falciparum (the causative agent of fatal malaria) contain high levels of polyamines during stages of rapid growth [6,7]. In Plasmodium spp, polyamine biosynthesis is uniquely characterised by the bifunctional arrangement of the ratelimiting decarboxylases, S-adenosylmethionine decarboxylase (PfAdoMetDC) and ornithine decarboxylase (PfODC) in a single protein, PfAdoMetDC/ODC [8].…”
Section: Introductionmentioning
confidence: 99%
“…Polyamine concentrations are strictly regulated on transcriptional, translational and post-translational levels as well as by uptake and efflux processes [1]. Erythrocytes infected by Plasmodium falciparum (the causative agent of fatal malaria) contain high levels of polyamines during stages of rapid growth [6,7]. In Plasmodium spp, polyamine biosynthesis is uniquely characterised by the bifunctional arrangement of the ratelimiting decarboxylases, S-adenosylmethionine decarboxylase (PfAdoMetDC) and ornithine decarboxylase (PfODC) in a single protein, PfAdoMetDC/ODC [8].…”
Section: Introductionmentioning
confidence: 99%
“…Assaraf et al (1984) showed that polyamine levels increased in parasite-infected erythrocytes. The authors determined a 95-fold increase in putrescine and a 51-fold increase in spermidine in trophozoite and schizont enriched fractions.…”
Section: Spermidine Biosynthesis and Metabolism In Plasmodium Falciparummentioning
confidence: 99%
“…The asexual intraerythrocytic form of the human malaria parasite, Plasmodium falciparum, has a high internal concentration of polyamines (Assaraf et al, 1984;Teng et al, 2009). The biosynthesis of polyamines by this parasite has some unusual features (Müller et al, 2000).…”
Section: Introductionmentioning
confidence: 99%